The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4209/aaqr.2013.10.0304
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Low Pressure Impactor Wall Deposits during Zinc Nanoparticle Sampling

Abstract: A Dekati® low pressure impactor (DLPI) is used to determine the mass distribution of airborne particles from 7 nm to 10 µm as a function of aerodynamic diameter. Quantification of wall deposits inside this sampling device was performed for the first time using polydisperse zinc aerosol produced by a thermal spraying process. This aerosol is more representative of the size distribution found in occupational atmospheres than aerosols usually produced in laboratories. Each experiment (3 replicates) was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The self-and cross-reactions of RO 2 radicals also form ROOR (C 16 H 22 O 10 ) or ROOR', which are the accretion products (Berndt et al, 2018;Molteni et al, 2018). The further O 2 adduct of BPR can form highly oxygenated RO 2 radicals and further react and finally form highly oxygenated organic molecules (HOMs; Types 1 and 2 in Scheme 1; Wang et al, 2017;Crounse et al, 2013;Ehn et al, 2014;Jokinen et al, 2015;Berndt et al, 2016). Dimethylphenol (C 8 H 10 O) and other products from the termination reaction with the benzene ring or double bond can react with OH radicals and further react to form HOMs as well.…”
Section: Proposed Mechanism Of Rh Effects On Soa Formationmentioning
confidence: 99%
“…The self-and cross-reactions of RO 2 radicals also form ROOR (C 16 H 22 O 10 ) or ROOR', which are the accretion products (Berndt et al, 2018;Molteni et al, 2018). The further O 2 adduct of BPR can form highly oxygenated RO 2 radicals and further react and finally form highly oxygenated organic molecules (HOMs; Types 1 and 2 in Scheme 1; Wang et al, 2017;Crounse et al, 2013;Ehn et al, 2014;Jokinen et al, 2015;Berndt et al, 2016). Dimethylphenol (C 8 H 10 O) and other products from the termination reaction with the benzene ring or double bond can react with OH radicals and further react to form HOMs as well.…”
Section: Proposed Mechanism Of Rh Effects On Soa Formationmentioning
confidence: 99%
“…et al, 2013b). In another study, 80 % of particle loss was found to concentrate around the nozzles and 20 % on the impaction plate in a stage of the DLPI (Dekati ® Low-Pressure Impactor) (Durand T. et al, 2014).…”
Section: Particle Loss Effectmentioning
confidence: 95%
“…Experimental and theoretical studies have been conducted for determining the particle losses by impaction and diffusion (Chen S.C. et al, 2007). The inertial loss of large particles normally occurs on the contractions which connect the big inlet tube to the small nozzle or on the surface of nozzle plate (Durand T. et al, 2014;Gupta T., 2015a, 2015b).…”
Section: Particle Loss Effectmentioning
confidence: 99%
See 2 more Smart Citations